COVID-19 and HSCT (Hematopoietic stem cell transplant). Issue 3 (September 2022) - Strasfeld, Lynne
Abstract: HSCT recipients are at increased risk for COVID-19-associated morbidity and mortality. Early treatment of symptomatic SARS-CoV-2 infection is an important means to decreasing risk for severe disease and death. While some HSCT recipients, particularly those who are early post-transplant and severely immunosuppressed, may have diminished response to COVID-19 vaccines, the benefits of vaccination are uncontested. Public health, healthcare facility and individual level approaches are all necessary to mitigate risk for infection in this vulnerable population.